The Lesson Learned from the New c.2547-1G > T Mutation Combined with p.R854Q: When a Type 2N Mutation Reveals a Quantitative von Willebrand Factor Defect - Casonato, Alessandra; Cozzi, Maria Rita; Ferrari, Silvia; Rubin, Beatrice; Gianesello, Lisa; De Marco, Luigi; Daidone, Viviana (Thrombosis and Haemostasis, 2022)
Type 2N is a rare von Willebrand disease (VWD) variant involving an impairment in the factor VIII (FVIII) carrier function of von Willebrand factor (VWF). It has a phenotype that mimics hemophilia A, and FVIII binding to VWF (VWF:FVIIIB) is tested to differentiate between the two disorders. Type 2N VWF defects may also be associated with quantitative VWF mutations (type 2N/type 1), further complicating the identification of cases. We report on a new quantitative VWF mutation (c.2547–1G > T) revealed by a p.R854Q type 2N mutation acting as homozygous despite being carried as a heterozygous defect. The proband had near-normal VWF levels (initially ruling out a defective VWF synthesis) and slightly reduced FVIII levels, while a VWF:FVIIIB test showed significantly reduced binding. Routine tests on type 2N homozygotes or heterozygotes combined with quantitative VWF defects in our cohort showed reduced FVIII levels in both groups, but it was only in the former that the FVIII/VWF antigen (VWF:Ag) ratio was always significantly reduced. The two tests are therefore not enough to identify all forms of type 2N VWD. While relatives of type 2N homozygotes usually have normal FVIII levels and FVIII/VWF:Ag ratios, relatives of type 2N/type 1 may have high FVIII/VWF:Ag ratios, but their VWF:FVIIIB and/or VWF:FVIIIB/VWF:Ag ratios are always low. Measuring FVIII and VWF levels may therefore suggest type 2N VWD in patients carrying type 2N mutations alone, but not in type 2N combined with quantitative VWF defects. The VWF:FVIIIB test should consequently be included when exploring VWF function, whatever VWD patient's phenotype.
Keywords: von Willebrand factor; type 2N von Willebrand disease; FVIII carrier function; VWF:FVIIIB; type 2N VWF mutations